NANDA-I, NIC, and NOC taxonomies, patients’ satisfaction, and nurses’ perception of the work environment: an Italian cross-sectional pilot study - Marcotullio, Alessia; Caponnetto, Valeria; La Cerra, Carmen; Toccaceli, Andrea; Lancia, Loreto (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Structured nursing care planning, patients’ satisfaction with care, nurses’ job satisfaction, and the characteristics of the work environment may influence each other and impact on the quality of hospital care. This study aimed at investigating the differences in nurses’ perception of the work environment and patients’ satisfaction with care, between two groups of hospital wards that used NANDA-I, NIC, and NOC taxonomies or not in the daily practice. Methods: A pilot cross-sectional study was conducted involving nurses employed in eight wards of a teaching hospital in central Italy and patients hospitalized in these wards. The ‘Nursing Work Index Revised’ and the ‘Patient Satisfaction Scale’ were used to investigate nurses’ perception of the work environment and patients’ satisfaction with care, respectively. Results: Significant better perceptions of both the constructs were highlighted in those wards that used nursing taxonomies. Conclusions: The application of a healthcare model based on the nursing process methodology should be empowered in the hospital settings, since it can influence the quality of the environment and patients’ satisfaction with care.